Friedrich Nietzsche's Impact on Modern German Literature Five Essays - Reichert, Herbert W. (UNC Studies in the Germanic Languages and Literatures, 1975)
These previously published essays discuss Nietzsche's influence on Arthur Schnitzler, Carl Sternheim, Georg Kaiser, Robert Musil, and Hermann Hesse. As a Festschrift, it also contains a tribute to Herbert W. Reichert and a bibliography of his writings.